Partnership and profit-sharing in islamic law - Siddiqi, Muhammad Nejatullah (United Kingdom : The Islamic Foundation, 1985)
Social Science
2004-11-04
Keywords: Islamic law; Partnership; Financial liabilities; Islamic countries